قياس أثر السياسة النقدية على النمو الاقتصادي في الجزائر خلال الفترة (1990 إلى 2021) باستخدام نموذج Ardl. - شرف, نصيرة; روشو, عبد القادر (جامعة الوادي - University of Eloued, 2023)
This study aims to estimate the impact of monetary policy on economic growth in Algeria during the period (1990-2021), where the Autoregressive Distributed Time Deceleration (ARDL) model was used in estimating the long-term relationship after making sure that there is a co-integration between the study variables,The results of the study indicated the effectiveness of monetary policy represented by the money supply in its broad sense in stimulating economic growth in Algeria in the long term, and the results of the short term indicated that economic growth is positivelyaffected by the increase in the money supply in its broad sense and the official exchange rate.
Measuring the impact of monetary policy on economic growth in Algeria During the period (1990 to 2021) using the ARDL model.
مقال
Keywords: أثر ; نمو اقتصادي ; سياسة نقدية ; الجزائر ; نموذج الانحدار الذاتي للإبطاء الزمني الموزع ARDL; impact;economic growth; monetary policy; Algeria; ARDL.